Peran persepsi keterlibatan orang tua terhadap keterampilan membaca siswa Sekolah Dasar - Zulfikar Lalomi; Ama, Roy Gustaf Tupen (PSYCOMEDIA : Jurnal Psikologi, 2024)
Reading skills are basic skills that students must have in order to support other subject matter. Reading modeling can help students improve their reading skills. This research aims to determine the relationship between perceptions of parental involvement and elementary school students' reading skills. The research method used is a correlational quantitative approach. In this study, scales were used, namely the reading skills scale and the perception scale of parental involvement. The population in this study were all students in grades 3, 4 and 5 at SDN Triharjo Sleman. The sampling technique used was probability sampling with a sample size of 103 students with sample criteria namely students in grades 3, 4 and 5, male and female and living with their parents. The analysis technique in this research uses the product moment correlation technique. The results of the analysis show that there is a relationship between perceptions of parental involvement and reading skills, r value = 0.716. The results of this study show that reading skills are in the high category at 89.3%, and perceptions of parental involvement are in the high category at 89.3%.